Efficient industrial dye decolorization by Bacillus sp. VUS with its enzyme system - Dawkar, Vishal V.; Jadhav, Umesh U.; Tamboli, Dhawal P.; Govindwar, Sanjay P. (Ecotoxicology and Environmental Safety, 2010)
This work presents role of different enzymes in decolorization of industrial dye Orange T4LL by Bacillus sp. VUS. Bacillus sp. strain VUS decolorized dye Orange T4LL, under static anoxic condition in 24 h. During decolorization of Orange T4LL a significant induction in the activities of lignin peroxidase, tyrosinase, and reductases (NADH-DCIP, azo, and riboflavin) was observed. The biodegradation was monitored by Ultraviolet-visible spectroscopy, Fourier transform infrared spectroscopy, and high performance liquid chromatography. The final products 4-methyl-2-o-tolylazo-benzene-1,3-diamine and [3-(phenyl-hydrazono)-cyclohexa-1,4-dienyl]-methanol were characterized by gas chromatography-mass spectroscopy. Phytotoxicity, COD, and BUD revealed non-toxicity of degraded products. Phytotoxicity study demonstrated non-toxicity of the biodegraded products for crop plants with respect to Triticum aestivum and Sorghum bicolor. Bacillus sp. VUS with its enzyme system could be a useful tool for textile effluent treatment. (C) 2010 Elsevier Inc. All rights reserved.
Keywords: Decolorization; GC-MS; Lignin peroxidase; Orange T4LL; Phytotoxicity; Reductases

Purification and characterization of bacterial aryl alcohol oxidase from sphingobacterium sp ATM and Its uses in textile dye decolorization - Tamboli, Dhawal P.; Telke, Amar A.; Dawkar, Vishal V.; Jadhav, Shekhar B.; Govindwar, Sanjay P. (Biotechnology and Bioprocess Engineering, 2011)
Aryl alcohol oxidase (AAO) produced by dye decolorizing bacteria Sphingobacterium sp. ATM, was purified 22.63 fold to a specific activity of 21.75 mu mol/min/mg protein using anion exchange and size exclusion chromatography. The molecular weight of the purified AAO was found to be 71 kDa using sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE), and confirmed by zymography of AAO using L-dopa. The enzyme showed substrate specificity towards veratryl alcohol, followed by n-propanol. The optimum pH and temperature of purified AAO were found to be 3.0 and 40 degrees C, respectively. The K(m) and V(max) of AAO was 1.1615 mM and 3.13 mM/min when veratryl alcohol was used as substrate. Sodium azide showed maximum inhibition while ethylenediamine tetra acetic acid (EDTA), L-cysteine and dithiothreitol showed slight inhibition. Metal ions also showed slight inhibition. HPLC analysis confirmed the degradation of Direct Red 5B. The metabolite obtained after decolorization of Direct Red 5B was characterized as 3 diazenyl 7 [-(phenyl carbonyl) amino] naphthalene-2-sulfonic acid using GC-MS analysis.
Keywords: aryl alcohol oxidase; Direct Red 5B; dye decolorization; ion exchange chromatography; Sphingobacterium sp ATM